2012
DOI: 10.1371/journal.pone.0047782
|View full text |Cite
|
Sign up to set email alerts
|

GWA Analysis for Milk Production Traits in Dairy Sheep and Genetic Support for a QTN Influencing Milk Protein Percentage in the LALBA Gene

Abstract: In this study, we used the Illumina OvineSNP50 BeadChip to conduct a genome-wide association (GWA) analysis for milk production traits in dairy sheep by analyzing a commercial population of Spanish Churra sheep. The studied population consisted of a total of 1,681 Churra ewes belonging to 16 half-sib families with available records for milk yield (MY), milk protein and fat yields (PY and FY) and milk protein and fat contents (PP and FP). The most significant association identified reached experiment-wise signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 49 publications
8
87
2
3
Order By: Relevance
“…For example, there were no CCR near the LALBA (alpha-lactalbumin) gene (OAR3∶137 Mb), where a particular variant has been recently been proposed to explain a QTL for milk protein percentage identified in Churra sheep [39]. The lack of signal near this QTL in the F ST analysis of Churra vs Ojalada is consistent with the fact that the causative mutation is still segregating in Churra, which allowed its identification as QTL.…”
Section: Discussionmentioning
confidence: 72%
“…For example, there were no CCR near the LALBA (alpha-lactalbumin) gene (OAR3∶137 Mb), where a particular variant has been recently been proposed to explain a QTL for milk protein percentage identified in Churra sheep [39]. The lack of signal near this QTL in the F ST analysis of Churra vs Ojalada is consistent with the fact that the causative mutation is still segregating in Churra, which allowed its identification as QTL.…”
Section: Discussionmentioning
confidence: 72%
“…These rams belonged to the Selection Nucleus of ANCHE and sired 1681 ewes from a commercial population previously analyzed in a genotyping project with the Illumina OvineSNP50 BeadChip (Garcia-Gamez et al 2012). As pedigree heads of this population, the 15 rams studied here were selected as an initial set of animals to assess the genetic variability of the MHC class II genomic region through sequencing analysis.…”
Section: Sheep Used For Sequencingmentioning
confidence: 99%
“…Compared to the complete cds of the sheep gene for alpha lactalbumin (GenBank AB052168) determined by Yamamoto (2000), three nucleotide variants are evident but not further described. Recently, García-Gámez et al (2012) re-identified one of those polymorphisms g.242T > C as the most likely causal mutation influencing milk protein percentage (GenBank NM 001009797.1). Comparing our results with this genomic reference variant (NM 001009797.1) three non-synonymous nucleotide exchanges were discovered.…”
Section: Laamentioning
confidence: 99%